A comparative survey on the effects of rhinoplasty on confidence and happiness - Hassanzadeh, Ziba; Mohammad Nezhady, Behjat; Zavar, Majid; Alipour, Parisa (Researcher Bulletin of Medical Sciences, 2019)
Introduction: With regard to the increasing aesthetic solutions through makeup and plastic surgeries, high rate of cosmetics sales in Iran, and increased office visit for plastic surgeries, the purpose of this study is to analysis the effect of rhinoplasty on self-confidence and happiness of women aged 16 to 35 who were visited in private clinics in Urmia city in December 2014. Materials and Methods: The study performed on 40 women who have undertaken rhinoplasty, 40 women who were waiting for rhinoplasty, and a group of 40 women who have not undergone rhinoplasty. Copper Smith self-esteem questionnaire including 58 questions and Oxford Happiness Questionnaire including 29 questions have been used in this study. Results: The results of student’s t-test for independent groups showed that from the aspects of self-esteem and happiness, there was a difference between the group who have done surgery and those who were standing by. Discussion and Conclusion: The findings show that self-esteem and happiness of the people who undergone rhinoplasty is equal and even more than those who were standing by for this operation or have not taken the operation.